Comparative efficacy of talquetamab vs. current treatments in the LocoMMotion and MoMMent studies in patients with triple-class-exposed relapsed/refractory multiple myeloma - Einsele, Hermann; Moreau, Philippe; Bahlis, Nizar; Bhutani, Manisha; Vincent, Laure; Karlin, Lionel; Perrot, Aurore; Goldschmidt, Hartmut; van de Donk, Niels W. C. J.; Ocio, Enrique M.; Martinez-Lopez, Joaquin; Rodríguez-Otero, Paula; et al. (Advances in therapy, 2024)
Talquetamab, a bispecific antibody targeting GPRC5D × CD3, is approved for the treatment of patients with triple-class -exposed (TCE) relapsed/refractory multiple myeloma (RRMM) on the basis of the results from the phase I/II MonumenTAL-1 trial. The relative effectiveness of talquetamab vs. real-world physician’s choice of therapy (RWPC) was assessed using adjusted comparisons.
Gesehen am 10.09.2024